KEBERLAKUAN ALASAN PANDEMI COVID-19 DALAM DUNIA KETENAGAKERJAAN - Marchelia, Andria; Apriliani, Dea; Anienda Tien, Mas (Jurnal Hukum Bisnis Bonum Commune, 2021)
AbstractThe COVID-19 pandemic is often used as an excuse for companies to take arbitrary actions that lead to disputes over rights between employers and workers. one of the problems that will arise is in the form of cutting wages to termination of employment which is carried out unilaterally by the company. Especially in the process the company carries out unilaterally contradicting existing laws and regulations. So the research aims to find out whether the COVID-19 pandemic can be used as an excuse for companies to cut wages and terminate employment of their workers as reviewed by Law of the Republic of Indonesia Number 13 of 2003 concerning Manpower and Law of the Republic of Indonesia No. 11 of 2020 concerning Job Creation., as well as implementing regulations. Thus, to protect the normative rights of workers, researchers conduct research related to legal issues using the juridical normative approach, where what is studied is the norms and laws being enforced in society.Keywords: COVID-19 pandemic; pay cuts; termination of employment; workersAbstrakPandemi COVID-19 dijadikan alasan perusahaan untuk melakukan tindakan sewenang-wenang yang menimbulkan adanya perselisihan hak antar pengusaha dan pekerja. Permasalahan yang muncul dari adanya perselisihan hak tersebut salah satunya berupa pemotongan upah hingga sampai pemutusan hubungan kerja secara sepihak oleh perusahaan. Terlebih dalam prosesnya yang dilakukan perusahaan dengan cara sepihak bertentang dengan peraturan perundang-undangan yang ada. Maka, penelitian bertujuan untuk mengetahui dapatkah Pandemi COVID-19 dijadikan alasan perusahaan untuk melakukan pemotongan upah dan pemutusan hubungan kerja terhadap pekerjanya yang ditinjau dari Undang-Undang Republik Indonesia Nomor 13 Tahun 2003 tentang Ketenagakerjaan, Undang-Undang Republik Indonesia Nomor 11 Tahun 2020 tentang Cipta Kerja, serta peraturan pelaksananya. Sehingga, untuk melindungi hak normatif dari pekerja, peneliti melakukan penelitian terkait isu hukum tersebut dengan menggunakan metode pendekatan yuridis normatif, dimana yang diteliti adalah norma dan peraturan perundang-undangan yang telah berlaku di masyarakat.